Chlorinated and brominated bisphenol A derivatives: Synthesis, characterization and determination in water samples. (December 2018) - Doumas, Manon; Rouillon, Steeve; Venisse, Nicolas; Nadeau, Cedric; Pierre Eugene, Pascale; Farce, Amaury; Chavatte, Philippe; Dupuis, Antoine; Migeot, Virginie; Carato, Pascal
Abstract: Bisphenol A (BPA) has been used in the plastics industry for several decades. During the treatment of drinking water with chlorine reagent, the formation of chlorinated derivatives of BPA (ClxBPA) but also bromoBPA and bromochloroBPA is to be expected. Some of these compounds are considered to have an estrogenic effect and could induce major risks for human health by targeting different organs and systems in the body. In this paper, we describe the synthesis of chloro- and bromobisphenol A (ClxBPA, BrxBPA, BrxClxBPA)and their analytical characterization. These derivatives could be used as analytical standards in LC-MS/MS or evaluated in in vitro biological tests for their potential as endocrine disruptors. In this study, we evaluated the presence of BPA, ClxBPA in a pilot study from water samples. Range values found for BPA, ClxBPA were respectively 2.8–4169.3 ng/L and 0.8–11.3 ng/L. Graphical abstract: Highlights: A series of bromo, chloro, and mixed bromochloro BPA compounds were synthesized. Compounds were characterized by 1 H NMR, 13 C NMR, LCMS and their purity >97%. These derivatives were used as analytical standards. Concentrations of BPA and Clx-BPA were measured in water samples from a pilot study. BPA and its chlorinated congeners Clx-BPA were detected in a majority of water samples.